Silence on the plate: revisiting the enigma of Mycobacterium leprae cultivation - Gotor-Rivera, Alfonso; Gutiérrez-Casado, Natalia; Acosta-Soto, Lucrecia (Frontiers in Microbiology, 2025)
IntroductionMycobacteriumleprae remains uncultivable in axenic media, a constraint that continues to hamper leprosy research. As research animals, such as mice or armadillos, are the only reproducible method of sustained laboratory growth, this is restricted to a few specialized laboratories. The development of axenic media would increase access to this field.MethodsWe performed a descriptive bibliographic review (May 2025) across PubMed, Embase, and the Cochrane Library using both controlled vocabulary and free terms related to M. leprae cultivation. After de-duplication and screening, 78 studies met the inclusion criteria.ResultsHistorically, claims of in vitro growth on egg-based or synthetic media have proven irreproducible or were subsequently attributed to non-leprae mycobacteria. Temperature and gas composition emerge as critical parameters: convergent evidence indicates thermosensitivity with optimal performance at 30–33 °C and deterioration at 37 °C; limited growth has been reported under microaerophilic atmospheres ( 2.5% O₂ with added CO₂), yet durable subculture remains unachieved. Cell-based systems—such as macrophages or Schwann cells, which are traditional targets in vivo of M. leprae—can preserve viability for weeks and occasionally increase bacterial counts, but continuous, exponential replication has not been demonstrated. Mechanistic insights from genomics, transcriptomics, and metabolomics suggest that while M. leprae presents extensive gene decay, many core biosynthetic pathways persist. Lipid droplets (LD), immunomodulators (e.g., IL-10, PGE₂, and IGF-I), and L-arginine/nitric oxide pathways appear to shape the intracellular fate of the bacterium. An alternative unifying hypothesis posits that failure in vitro reflects structural fragility rather than a single auxotrophy, with host-derived factors (e.g., LDs and iron delivery) transiently compensating in vivo.DiscussionTo date, no reproducible, cell-free culture system exists. This review aims to provide a starting point for future research into this objective. Achieving a reproducible in vitro culture of Hansen’s bacilli would represent a major advance in the field of leprology and would significantly accelerate translational research in this disease.